The Mediatization of Politics. From the National to the Transnational - Trenz, Hans-Jörg; Michailidou, Asimina (PARTECIPAZIONE E CONFLITTO, 2014)
The mediatization of politics is generally explained in relation to the legitimacy requirements of the modern state and as such, it is typically confined to the national media sphere. Can we speak in any meaningful way of mediatization beyond the national? The European Union (EU), which operates under increasing legitimacy constraints and is exposed to the salience of media debates that contest its public legitimacy, is a case in point. Is the EU becoming mediatized? And what are the effects of EU mediatization? Under what conditions can the mass media become a facilitator of European integration? The issue at stake is whether the media (new and old) can have an integration function beyond the national and facilitate the building of democratic legitimacy of the European Union. We propose that the concept of mediatization offers the theoretical and analytical tools necessary to understand precisely how the interaction between the EU polity and the media unfolds and how it impacts on the process of the EU’s public legitimation. First we deliver a general account of mediatization, highlighting its core definers and main points of critique that the concept has attracted. We then show how mediatization is relevant to the EU polity and propose an analytical model that can capture this process empirically